Flow cytometry isolation and reverse transcriptase-polymerase chain reaction characterization of human round spermatids in infertile patients - Ziyyat, A; Lassalle, B; Testart, J; Briot, P; Amar, E; Finaz, C; Lefèvre, A (Human reproduction (Oxford), 1999)
Flow cytometry coupled to cell sorting is proposed as a method to isolate round spermatids from testicular biopsies in obstructive azoospermic patients. The cells were separated on the basis of their size and density only. We obtained homogenous populations of alive round spermatids free of lymphocytes and diploid germ cells. The detection of protamine 1 gene (PRM1) and PRM2 expression in the sorted cells proves that these cells are round spermatids. On the contrary, neither the expression of CD3-delta, which is specific to lymphoid cells, nor that of MAGE1, which has been demonstrated in diploid germ cells, could be observed in the round spermatid population even after using a nested polymerase chain reaction (PCR) assay. The flow cytometry procedure failed to isolate round spermatids from ejaculates in non-obstructive azoospermic patients. In > 39 ejaculates tested by reverse transcriptase-PCR, only nine revealed the presence of some round spermatids, as demonstrated by the expression of PRM1. However, these round spermatids did not express PRM2.